Integration of Combined Transport into Supply Chain Concepts Simulation-based Potential Analysis and Practical Guidance - Bendul, Julia; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2014)
Recent supply chain concepts are characterized by attempts to reduce inventory and to simultaneously increase flexibility and reliability. The analysis of recent SC concepts shows that transport actors are often not integrated members of these SC concepts. Julia Bendul exploits this imperfection for the integration of combined road and rail transport into supply chain concepts – even for distances below 100 km. Supported by a simulation study the author shows that the tight integration of material and information flows opens up time buffers and increases coordination flexibility, which is necessary for combined transport integration. Therefore, she provides processes, methods and instruments for 1) planning and control, 2) network and organizational structure, 3) process design, 4) information & communication technology as well as 5) material flow structure, which support the combined transport integration into supply chain concepts.   Contents Internal and external challenges of combined transport integration Adjustment of procurement, production and distribution concept elements to combined transport - cause-and-effect relationships Situation-specific choice of technical and organizational measures ·         Impact of supply chain concept adaptations on classical and innovative supply chain management objectives   Target Groups ·         Researchers and students of business administration and industrial engineering ·         Practitioners from industry, trade and logistics service   The author Julia Bendul was a research assistant at the Chair of Logistics Management at the University of St.Gallen. Before joining the Jacobs University Bremen as Assistant Professor of Network Optimization in Production and Logistics in 2013 she was working as a Business Consultant at an automobile manufacturer.  .
Integration of Combined Transport into Sypply Chain Concepts from a Performance Perspective: Need for Action -- Problem Concretisation: SCP Orientation Encourages the Integration of CT into SC Concepts -- CT as an Element of SC Concepts -- Conceptual Research Framework of Performance-oriented CT Integration into SC Concepts.-Performance-oriented Integration of Combined Line Transport into a Lean SC: A Simulation Study -- Implications for Science and Practice.
Keywords: Production management; Operations Management